Paradoxical Utopia: The Millennium Villages Project in Theory and Practice. (22nd September 2015) - Wilson, Japhy
Abstract : The Millennium Villages Project (MVP) aims to achieve the Millennium Development Goals in villages across sub‐Saharan Africa, through an integrated set of interventions designed to catalyse the transformation of 'sub‐subsistence farmers' into 'small‐scale entrepreneurs'. I conceptualize the MVP as a paradoxical utopia, which is attempting to socially produce the supposedly natural order of a market society, through the staging of a fantasy of harmonious capitalist development that misrepresents the realities of rural African capitalism. Drawing on field research conducted in the Millennium Villages of Ruhiira, Uganda, and Bonsaaso, Ghana, I show how the conceptual failings of the MVP have led to the elite capture of project inputs, the absence of inclusive participation and a lack of long‐term sustainability. In Ruhiira, the MVP has contributed to the consolidation of existing relations of inequality, while in Bonsaaso it has been overwhelmed by an influx of foreign gold miners. Through its failure to stage its fantasy of capitalist development in these cases, the MVP has paradoxically succeeded in consolidating the actual social relations of capitalism.